Prostate cancer patient’s survival in Lithuania - Giedrė Smailytė; Robertas Adomaitis; Karolis Ulinskas; Birutė Aleknavičienė (Acta Medica Lituanica, 2013)
Background. The aim of this study was to evaluate changes in the survival of prostate cancer patients during the 12-year period and to analyze differences in survival by period of diagnosis, stage of disease, age and place of residence. Materials and methods. All newly diagnosed cases of prostate cancer (ICD-10, C61) in men were identified in the Lithuanian Cancer Registry for the period 1994–2005. Five-year relative survival estimates were computed with the Hakulinen method using the STATA software. Five-year relative survival estimates were calculated for three different periods of time when prostate cancer was diagnosed (1994–1997, 1998–2001 and 2002–2005), by age (15–59, 60–74, and 75–99), stage at diagnosis (I, II, III, IV, unknown) and place of residence (cities and towns or rural areas). Results. The survival of prostate cancer patients in Lithuania has dramatically increased. Five-year relative survival in the period 1994–1997 was 46.92% and in the period 2002–2005 it reached 86.49%. Medium age prostate cancer patients (60–74 years) compared to younger and older patients had better survival rates. Increasing survival was observed for all stages of disease. Lower five-year relative survival rate of prostate cancer patients was reported for men from villages or other rural areas compared to patients from cities and towns in all periods under study. Conclusions. The five-year survival rate of patients with prostate cancer has increased from 46.92% (95% CI 44.12–49.74) in 1994–1997 to 86.49% (95% CI 84.73–88.22) in 2002–2005 in Lithuania. The study identified survival differences by age and place of residence. Issues, such as access to care, quality of medical care, must be made equally available and accessible for the whole population with special attention to older men and men living in rural areas.